“I Trust in Staff's Creativity”—The Impact of COVID-19 Lockdowns on Physical Activity Promotion in Nursing Homes Through the Lenses of Organizational Sociology - Frahsa, Annika; Altmeier, Dorothee; John, Jannika M.; Gropper, Hannes; Granz, Hanna; Pomiersky, Rebekka; Haigis, Daniel; Eschweiler, Gerhard W.; Nieß, Andreas M.; Sudeck, Gorden; Thiel, Ansgar (Frontiers in Sports and Active Living, 2020)
Objectives: The health-enhancing benefits or regular physical activity (PA) reach into old age. With the emergence of the coronavirus disease of 2019 (COVID-19) pandemic and the associated national lockdowns and restrictions, nursing home residents were restrained from being physically active. In our study, we aimed to assess the impact of the COVID-19-related restrictions on PA promotion in nursing homes from an organizational-sociological lens. Methods: We collected data in eight nursing homes in Germany. Data collection included (i) semistructured interviews focusing on COVID-19-related restrictions and their effects on nursing homes from the home administrators' perspectives; (ii) open-ended surveys with nursing home staff and relatives focusing on daily routines and contact restrictions; and (iii) collection of documents such as care concepts, mission statements, and weekly activity plans. We analyzed all data with a reflexive thematic analysis approach. Results: We identified three stages of COVID-19-related changes in nursing homes that impacted PA promotion, as follows: (1) external closure and search for emergency control, (2) organizational adaptations to create a livable daily life in the internal environment, and (3) slow reintegration of interactions with the external organizational environment. Document analysis revealed that PA promotion was not part of decision programs or internal staff work descriptions. Rather, PA promotion was delegated to external service providers. The assignment of PA promotion to external providers was not structurally anchored in decision programs, which makes PA promotion not sustainable, particularly during unforeseen events that limit access to the organization. During the pandemic, executive staff believed in internal staff to buffer competencies with regard to PA promotion. Thus, executive staff often considered PA promotion relevant, even during the pandemic, but thought that PA promotion is a task that can be fulfilled by unqualified but motivated internal staff. Conclusion: While our study participants showed a high level of coping-capacity belief, it remains unclear which long-term impacts of COVID-19 on PA promotion in nursing homes are to be expected. At the practice level, executive staff in nursing homes that aim to promote PA within their organization should become aware that PA promotion needs to be incorporated into organizational structures to be implemented and continued in challenging times such as in a pandemic.